Diagnosis and treatment of hepatocellular carcinoma with pelvic metastasis expressing AFP: a case report - Huang, Legang; Wang, Zijie; Lu, Jiankuan (Frontiers in Oncology, 2025)
This report presents the case of a 68-year-old female patient with hepatocellular carcinoma (HCC) who experienced persistently elevated alpha-fetoprotein (AFP) levels following resection of the primary liver tumor. The patient had previously undergone transcatheter arterial chemoembolization (TACE) and liver tumor resection, but postoperative AFP levels continued to rise, suggesting the possibility of extrahepatic metastasis. PET-CT scans revealed an irregular soft tissue mass in the recto-uterine pouch, which was later confirmed as a HCC metastasis through needle biopsy. The patient subsequently received radioactive seed implantation therapy, leading to a significant decrease in AFP levels. This case highlights the rarity of isolated pelvic metastasis in HCC patients and underscores the importance of AFP in postoperative monitoring. The combination of PET-CT imaging and pathological biopsy is instrumental in improving the detection rate of HCC metastases, enabling more accurate treatment planning for patients.